(untitled) (Al-Qamar, 2021)
Infertility is a phenomenon that not only gives tough time to females but it equally affects male partners. Due to the quiet nature of males and communication gap with female partners they tend to hide their feelings of being incomplete and being not sharing these things could develop thoughts of suicide and can drag them to endless emotions of depression. While discussing the sexual and reproductive health noting all the facts and figures regarding maternal mortality and factors leading towards couple’s fertility it becomes necessary to discuss infertility in detail and conceptualizing this phenomenon from perspective of religion. From clinical point of view, number of couples seeking help in conceiving fall under the criteria of infertility. Although there many reasons behind infertility as sexual history, age etc. but in this paper male infertility is the focus that sub fertile men have missing Y-chromosome, which effects the number of sperms and passes the infertility to the off springs. ICSI born child are affected by abnormal structure of chromosome and increased sex chromosome disorders.